"How to Give a Killer Pitch?" Performances of Entrepreneurial Narratives as Identity Models in Higher Education. (July 2020) - Komulainen, Katri; Siivonen, Päivi; Kasanen, Kati; Räty, Hannu
In this ethnographic research, we explore the entrepreneurial narratives performed by entrepreneurs (from outside academia) as desirable identity-building models for Finnish university students during an Entrepreneurship Week course. We also reflect on the accessibility of these identity models for students in terms of gender, class, and education. Our analysis shows that, although the entrepreneurs were positioned as role models for all students, through performances of masculine entrepreneurial identities with certain kinds of special talents and social divisions between groups (i.e., female entrepreneurs, wageworkers, and researchers in ivory towers ), it was apparent that not all university students are entrepreneurial types. In addition, the performed narratives challenged the traditional interpretations of what it means to be an academically educated graduate in working life (e.g., in terms of upward mobility). We conclude that Entrepreneurship Week was more about training an entrepreneurial workforce than acquiring skills needed in business. Our study provides a critical perspective both on how neoliberal governance operates in entrepreneurship education and on what kinds of entrepreneurial identities future higher education graduates should possess. We suggest that academics should take an active role in creating more inclusive narratives and identity-building models for academic entrepreneurship.